2012
DOI: 10.1128/mcb.00636-12
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Insulin Signaling by the Phosphatidylinositol 3,4,5-Triphosphate Phosphatase SKIP through the Scaffolding Function of Pak1

Abstract: Skeletal muscle and kidney-enriched inositol polyphosphate phosphatase (SKIP) has previously been implicated in the regulation of insulin signaling in skeletal muscle. Here, we present the first report of the mechanisms by which SKIP specifically suppresses insulin signaling and the subsequent glucose uptake. Upon insulin stimulation, SKIP is translocated to the membrane ruffles, where it binds to the active form of Pak1, which mediates multiple protein complex formation with phosphatidylinositol 3,4,5-triphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…Among the main canonical ER stress transducers, ATF6 and the IRE1-XBP1 system are likely to be essential for the expression of the genes involved in lipid biosynthesis and protein folding, including GRP78. Our previous results have shown that an accumulation of SKIP at the plasma membrane contributes to the suppression of insulin signaling and glucose uptake; membrane-localized SKIP interacts with an active Pak1, leading to the hydrolysis of PIP 3 bound to Akt2 and PDK1 (3). Accumulation of SKIP in proximity to these PIP 3 effectors might mediate an effective inhibition of insulin signaling under ER-stressed conditions.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Among the main canonical ER stress transducers, ATF6 and the IRE1-XBP1 system are likely to be essential for the expression of the genes involved in lipid biosynthesis and protein folding, including GRP78. Our previous results have shown that an accumulation of SKIP at the plasma membrane contributes to the suppression of insulin signaling and glucose uptake; membrane-localized SKIP interacts with an active Pak1, leading to the hydrolysis of PIP 3 bound to Akt2 and PDK1 (3). Accumulation of SKIP in proximity to these PIP 3 effectors might mediate an effective inhibition of insulin signaling under ER-stressed conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Akt2 phosphorylation at Thr-309 and Ser-474 was measured as described previously (3). Cell lysates were immunoprecipitated with Akt2 antibody for 1 h at 4°C, and immunoprecipitates were washed with wash buffer containing 20 mM Tris-HCl (pH 7.4), 150 mM NaCl, 50 mM NaF, 1 mM Na 3 VO 4 , and 1 mM PMSF 5 times before they were analyzed by Western blotting using antibodies for phospho-Akt (Thr-308) or phospho-Akt (Ser-473).…”
Section: Fig 1 Continuedmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, we have shown that PAK1 is essential to whole-body glucose homeostasis given its unique role in both pancreatic β-cells and skeletal muscle 19 . Recent work by others also highlighted the importance of PAK1 in insulin secretion 39 and insulin signaling 40 . Consistent with a special requirement for PAK1 in insulin signaling, mRNA levels of PAK1 are significantly reduced in soleus and gastrocnemius skeletal muscle from obese diabetes-susceptible mice 41 .…”
Section: Discussionmentioning
confidence: 93%
“…However, other metabolic tissues such as liver, brown fat and brain were not examined and may contribute to the phenotype [77]. Interestingly, SKIP inhibits insulin-induced Akt signalling via complex formation with the scaffolding protein Pak1, to promote PtdIns(3,4,5)P 3 degradation and disassociation of the PDK1-Akt complex [78]. Therefore, this data suggest SKIPmediated PtdIns(3,4,5)P 3 hydrolysis controls insulin-induced Akt signalling that may not be significantly affected by increased PtdIns(3,4)P 2 signals.…”
Section: Skip a 5-phosphatase That Regulates Metabolic Akt Signallingmentioning
confidence: 99%